Mortality Reimagined: Going through Deleuze’s Encounter with Death - Sariyar Murat (Open Theology)
Deleuze’s philosophy, celebrated for its affirmation of life, also offers a profound and nuanced exploration of death, challenging conventional understandings of individuality and existence. Through key concepts such as the “death drive,” the “virtual,” and “assemblage,” Deleuze frames death not as a terminus, but as an integral process within life itself. This article critically examines Deleuze’s conception of death in three main stages. First, I explore how Deleuze characterizes the ego as a metastable entity – inherently fragile and prone to disintegration. This implies that we are always already embedded in processes that draw us into larger becomings, dissolving fixed identities. Next, I differentiate this perspective from spiritual traditions that emphasize ego dissolution. I argue that Deleuze’s framework, while grounded in a secular, intellectual engagement with worldly involvement, offers insights that could enrich spiritual discourse. Finally, I also identify limitations in his approach. Deleuze’s intense focus on the creation of the new often overlooks what he terms the “first death,” which aligns with traditional conceptions of mortality as an absolute end. He appears to neglect the possibility of a final cessation of all processes, such as the heat death of the cosmos. After presenting the practical implications of these considerations for religious life, I conclude by addressing various points of contact between these reflections and other intellectual currents. While Deleuze’s philosophy may not serve as a definitive framework for understanding death, engaging with his ideas provides insightful and novel perspectives on existence. It encourages a reexamination of the boundaries between life and death from an immanent standpoint, enriching traditional perspectives.